2002
DOI: 10.1074/jbc.m203354200
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae RNA Polymerase II Is Affected by Kluyveromyces lactis Zymocin

Abstract: The G 1 arrest imposed by Kluyveromyces lactis zymocin on Saccharomyces cerevisiae cells requires a functional RNA polymerase II (pol II) Elongator complex. In studying a link between zymocin and pol II, progressively truncating the carboxyl-terminal domain (CTD) of pol II was found to result in zymocin hypersensitivity as did mutations in four different CTD kinase genes. Consistent with the notion that Elongator preferentially associates with hyperphosphorylated (II0) rather than hypophosphorylated (IIA) pol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…In all cases, the mutant cells exhibited zymocin hypersensitivity. Moreover, hypersensitivity was also caused by truncation of the RNAPII CTD itself, further supporting the idea that a functional link between zymocin and RNAPII exists (13).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In all cases, the mutant cells exhibited zymocin hypersensitivity. Moreover, hypersensitivity was also caused by truncation of the RNAPII CTD itself, further supporting the idea that a functional link between zymocin and RNAPII exists (13).…”
supporting
confidence: 53%
“…In apparent agreement with this idea, low resolution hybridization showed that global poly(A) ϩ mRNA levels generally decline in the presence of zymocin, and Northern blot analysis showed significantly reduced levels of specific RNAPII-generated transcripts (3,5). In an attempt to further reinforce the notion that zymocin action is linked to RNAPII, Jablonowski and Schaffrath studied the effects on zymocin toxicity of genetic conditions that would be supposed to directly impair polymerase activity, such as mutations in the RNAPII kinase encoded by the BUR1/BUR2 genes, deletion of the SRB10 CTD kinase gene, and inactivation of the kinase activity of TFIIH (13). In all cases, the mutant cells exhibited zymocin hypersensitivity.…”
mentioning
confidence: 99%
“…Instead, its function may be modified in such a way that pol II activity is poisoned. Data indicating down-regulation of pol II-dependent transcription in the presence of zymocin, expression of partial zymocin resistance on overproduction of Fcp1p -a phosphatase that acts on the C-terminal domain (CTD) of the largest subunit of pol II -and possible interference of zymocin with recycling of pol II all support this notion (Jablonowski et al 2001b;Jablonowski and Schaffrath 2002).…”
Section: Introductionmentioning
confidence: 60%
“…Together with the finding that the TOT function can be dissociated from Elongator by mutagenesis of its HAT gene without affecting other Elongator properties (9), the HAT function of Elongator plays a key role in mediating zymocicity. As judged from the observations that (i) pol II-driven transcription is down-regulated in zymocin-treated cells (8,9), (ii) pol II underassembly and general pol II defects elicit zymocin-hypersensitivity (9,28), (iii) interfering with pol II C-terminal domain (CTD) modification alters the response of a cell to zymocin (9), and (iv) the phospho-states of pol II are imbalanced in zymocin-treated cells (29), zymocin may work by hijacking the TOT function of Elongator to convert it into a global pol II inhibitor. Genetic analyses have shown that deletion of any one of the ELP/TOT genes phenocopies the full range of elp/tot phenotypes induced by elp3 point mutations that drastically reduce the HAT activity of Elongator (8,12,25).…”
mentioning
confidence: 99%